WNT10A mutations also associated with agenesis of the maxillary permanent canines, a separate entity - P. Kantaputra (2018)
Agenesis or isolated hypodontia of the maxillary permanent canines is a very rare dental anomaly. We report on nine unrelated Thai patients with this condition. Three of them had one affected parent. Three heterozygous missense mutations (p.Arg171Cys; p.Gly213Ser; and IVS2+1G > A) were identified in WNT10A in six patients. The p.Gly213Cys mutation was found in four patients. One of the patients who had p.Gly213Ser mutation also had peg-shaped (microdontia of the) maxillary lateral incisors with dens invaginatus. The mothers of two patients who carried the same mutation as their affected sons (p.Gly213Ser and p.Arg171Cys) had microdontia of the maxillary permanent lateral incisor. Our study has demonstrated for the first time that agenesis of the maxillary permanent canines is a distinct entity, associated with mutations in WNT10A. Inheritance appears to be autosomal dominant. Agenesis of the maxillary permanent canines may accompany by microdontia of the maxillary permanent lateral incisors and dens invaginatus of the maxillary permanent lateral incisors. Mutations could not be identified in the coding exons of WNT10A in three patients. They might be located outside the coding exons, including the promoter regions. However, it is likely that agenesis of the maxillary permanent canines is a heterogeneous disorder. © 2013 Wiley Periodicals, Inc.